Safety issues of monoclonal antibodies used in rheumatology - A. V. Philippova; A. S. Kolbin; E. V. Verbitskaya; S. V. Glagolev; V. A. Polivanov; V. I. Mazurov; R. R. Samigullina (Izdatelstvo OKI, 2020)
Success in practical rheumatology of the latest decade achieved mainly due to monoclonal antibodies (MABs) appearance in routine medical practice. At the same time, the experience of practical application of MABs is limited both by observation period and exposure and their clinical and pharmacological properties do not allow to fully characterizing their safety profile with the data from clinical studies. The use of MABs is associated with the risk of delayed adverse drug reactions (ADRs) - types B (immunoallergic reactions), C (new diseases) and D (delayed teratogenic and oncogenic effects). Determination of risk factors in real medical evidence is especially important. The risk factors of ADRs including serious ADRs were studied based on an analysis of the spontaneous reports database of the Federal Service for Supervision in Healthcare and the data from rheumatologic register of patients receiving MABs - the E.E. Eikhvald Clinic in North-Western State Medical University named after I.I. Mechnikov. It was shown that the factors coming from the patient (gender, age group) do not affect the severity of the risk of occurrence of ADR, including serious ADRs, while the risk factor for monoclonal antibodies can be considered the choice of tocilizumab, which increases the risk of serious ADRs.